Challenges facing HIV treatment as prevention in Brazil: an analysis drawing on literature on testing - Monteiro, Simone (2019)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Educação em Ambiente e Saúde. Rio de Janeiro, RJ, Brasil.